2018
DOI: 10.1002/jcb.27337
|View full text |Cite
|
Sign up to set email alerts
|

The expression of ubiquitin‐specific peptidase 8 and its prognostic role in patients with breast cancer

Abstract: Our results demonstrated that USP8 might predict better clinical characteristics and might be a protective factor for patients with BC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…17 However, USP8 is down-regulated in breast cancer tissues, compared with that in normal breast tissues, and the high-expression of USP8 is correlated with better clinical features of breast cancer patients. 18 The reasons for the difference among these studies remained to be elucidated. The expression difference of USP8 in NSCLC tissues and normal tissues, as well as the correlation analysis with clinical characteristics of NSCLC patients, are also our future research directions.…”
Section: Discussionmentioning
confidence: 99%
“…17 However, USP8 is down-regulated in breast cancer tissues, compared with that in normal breast tissues, and the high-expression of USP8 is correlated with better clinical features of breast cancer patients. 18 The reasons for the difference among these studies remained to be elucidated. The expression difference of USP8 in NSCLC tissues and normal tissues, as well as the correlation analysis with clinical characteristics of NSCLC patients, are also our future research directions.…”
Section: Discussionmentioning
confidence: 99%
“…13 Notably, the activity of DUBs directly affects the turnover rate, activity, regeneration and localization of various proteins in cells. 14 Among these DUBs, ubiquitin-specific protease 8 (USP8) was demonstrated to be involved in breast cancer, 15,16 lung cancer, 17 corticotroph adenomas 18,19 and pituitary adenomas, 19,20 and these studies suggested that USP8 played an important role in different types of cancer. Nevertheless, no study has reported the impact of USP8 on GC.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to most tumors in which immunode cient tumor environment is associated with less favorable tumor behavior [44], CTAs with USP8 mutation and "cold" iTME are smaller in size [16] and have high remission rates after surgery [17,20,21]. Our ndings suggest that the favorable outcome of patients with USP8-mutated corticotroph adenomas is not immune-response dependent.…”
Section: Discussionmentioning
confidence: 72%
“…USP8 was also studied in the context of several other tumors. In breast cancer, high expression of USP8 was associated with better outcomes [21]. However, expression of USP8 in lung adenocarcinoma [22] and cervical squamous cell carcinoma [23] was associated with poorer outcomes compared with USP8negative tumors.…”
Section: Introductionmentioning
confidence: 99%